PERAN GURU DALAM MENGATASI KESULITAN BELAJAR PESERTA DIDIK DI SD - Mahzunia Fauziah Safitri; Afakhrul Masub Bakhtiar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
In the learning process, both teachers and students want satisfactory results. But in reality, something that is desired sometimes does not go well. There are still many students who encounter obstacles in learning so that it makes students have difficulty learning. Learning difficulties are conditions where students have obstacles or distractions in the learning process so that the expected results are not satisfactory. These obstacles or disturbances can be caused by several factors, both internal factors of students and external factors of students. Learning difficulties become an obstacle for teachers when delivering subject matter. Teachers have an important role for students in overcoming learning difficulties. As for the efforts made by the teacher to overcome learning difficulties, namely by identifying obstacles related to student learning difficulties, providing direction to student guardians to overcome problems, and finally the teacher provides study guidance to students.